Working in Partnership to Develop, Implement and Evaluate a Skills Based Group for People with Bipolar Disorder/Schizoaffective Disorder - B, Oliver (International Journal of Psychosocial Rehabilitation, 2013)
Aim: The present study involved collaborating with service users in the development, implementation and evaluation of a pilot skills based group intervention for individuals with bipolar disorder or schizoaffective disorder. Method: The intervention was integrated into the service as an adjunct to current treatment regimes in three community adult mental health teams. Two focus groups were initially conducted with thirteen multidisciplinary team members in order to explore their experi- ences of working with individuals with bipolar disorder/schizoaffective disorder and to inform the design of the subsequent interven- tion. The second phase of the study involved working with service users. There were eight participants in the design group (seven of which attended two focus groups in order to outline the design of the intervention); nine participants in intervention only group and six participants in the treatment as usual group. Those in the design and intervention only groups were invited to receive the six week skills group intervention which was designed on the basis of the two focus groups conducted with the design group. In addition to drawing on the experiences of service users, the intervention drew on various manualised and internet based resources using experiential and didact- ic approaches. Results: Qualitative findings indicated that service user involvement in service planning is crucial as they have a unique insight into ser- vices and their views may differ from that of professionals. Improvements in self-reported self-esteem and self-efficacy were reported by individuals post intervention during qualitative feedback sessions. Conclusion: Future research is needed with a large sample size to examine if statistically significant gains are made and sustained and to further involve service users in decisions and facilitation of interventions.